You Can't Tell the Players With a Scorecard - Wriston, Walter B. (Tufts Archival Research Center, 2007)
This document was created from the speech, "You Can't Tell the Players With a Scorecard," written by Walter B. Wriston for the Securities Industry Association Luncheon on 21 January 1981. The original speech is located in MS134.001.004.00025.